Polariton physics : from dynamic Bose-Einstein condensates in strongly-coupled light-matter systems to polariton lasers /: from dynamic Bose-Einstein condensates in strongly-coupled light-matter systems to polariton lasers. (©2020) - Unknown
No abstract available